Global pandemic and state responses. Political feasibility for a “de-commodified” well-being in Latin America.: Global pandemic and state responses. Political feasibility for a “de-commodified” well-being in Latin America. - AGUILÓ, Juan Carlos (Utopía y Praxis Latinoamericana, 2021)
We had tried to argue about the impact of the global pandemic over the Latin American societies and States and by doing a brief summary about the states capacities and current level of welfare analyze the political possibilities for building a new goal of welfare and solidarity guaranteed by collective regulations.